2013
DOI: 10.3386/w19608
|View full text |Cite
|
Sign up to set email alerts
|

Russia's Fiscal Gap

Abstract: This paper is dedicated to the memory of Yegor Gaidar, who founded the Gaidar Institute and for whom fiscal sustainability and responsibility was of paramount importance. The views expressed herein are those of the author and do not necessarily reflect the views of the National Bureau of Economic Research. At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w19608.ack NBER working papers ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
3
0
3
Order By: Relevance
“…In comparison with 2013, the real revenues of the budget system in 2016 were lower by 15% than the Russian government had expected. The problems in revenue budget arose before 2014 (Goryunov et al 2013) and prior to the drop in the price of oil. Goryunov et al (2013) suggested that the predicted long-term budget revenue has been exceeded by expected long-term budget expenses, which has resulted in a budget gap 8.4% the size of GDP.…”
Section: Data Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with 2013, the real revenues of the budget system in 2016 were lower by 15% than the Russian government had expected. The problems in revenue budget arose before 2014 (Goryunov et al 2013) and prior to the drop in the price of oil. Goryunov et al (2013) suggested that the predicted long-term budget revenue has been exceeded by expected long-term budget expenses, which has resulted in a budget gap 8.4% the size of GDP.…”
Section: Data Issuesmentioning
confidence: 99%
“…The problems in revenue budget arose before 2014 (Goryunov et al 2013) and prior to the drop in the price of oil. Goryunov et al (2013) suggested that the predicted long-term budget revenue has been exceeded by expected long-term budget expenses, which has resulted in a budget gap 8.4% the size of GDP. Goryunov et al (2015) claimed that the budget gap has extended to 13.6% of GDP, which was caused by the decline in oil prices in 2014.…”
Section: Data Issuesmentioning
confidence: 99%
“…При сохранении текущего уровня расходов российский бюджет может стать профицитным только при быстром росте экономики и росте цен на нефть. Более того, по некоторым расчетам, обязательства, взятые российским руковод-ством на будущее, означают огромные бюджетные дефициты в будущем -даже без всякого кризиса (см., например, (Goryunov et al, 2013)). Да и ожидать восстановления экономики не приходится -даже в маловероятном случае снятия санкций структурные проблемы, вызвавшие замедление, начавшееся в 2008 или в 2013 г., никуда не уйдут, и российская экономика обречена на многолетнюю стагнацию.…”
Section: возможности бюджетной политикиunclassified
“…Однако недавно появились ис-следования, которые наглядно демонстрируют, что в сфере государственных финансов Россий-ской Федерации имеются серьезные проблемы. Так, в докладе [14] отмечено, что в России суще-ствует значительный бюджетный разрыв: нако-пленная разница между текущей стоимостью всех будущих расходов и доходов бюджета составляет 890 трлн руб. (28 трлн долл.…”
Section: проблемы системы управления государственным долгом россии сиunclassified
“…Помимо долговых ко-эффициентов, необходимо задействовать метод анализа нагрузки на государственный бюджет в долгосрочном периоде с учетом демографиче-ских изменений, примененный в работе [14].…”
unclassified